Critical Review of Harun Hadiwijono's Concept of Sekutu in Iman Kristen - Bima Adi (Sekolah Tinggi Teologi Kalimantan, 2020)
Harun Hadiwijono’s Iman Kristen describes God as the sekutu (ally) of man, and man as the sekutu (ally) of God. In Harun’s claim, he formulated his book in popular form, unlike other dogmatics writings, considering an extended readership beyond Christians. By the time the readers read the book, he said, they will find out that it has its own place among those preceding books. Whether it is good or not, it is up to those who will judge it. Those words from Harun provide the impetus for this study. Indeed, Iman Kristen is a tremendous writing on systematic theology. However, for me, Iman Kristen is not a contextual systematic theology opus. It is, more or less, a “product” that indicates the influence of colonial mentality and the narrowness of the theology of the missionaries’ vision in the past. In my conclusion, Harun was not aware of the danger of depicting the relation between God and humankind, and vice versa with the term sekutu. In short, it is indeed original and unique, yet brings many problems which are not even being realized by Christians in Indonesia.